Basis of Efficient Cash Flow Management of the Enterprise - Eshonqulov Akmal Qudratovich (International Journal on Economics, Finance and Sustainable Development, 2022)
The urgency of the problem of managing the cash flows of organizations is of particular importance today. Cash flow management is a necessary tool for making a profit for any organization.